2009
DOI: 10.1002/fam.1004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a phosphorus‐based FR, a nanoclay and PA6—Part 1: Interaction of FR and nanoclay

Abstract: SUMMARYThe thermal decomposition of organophosphorus fire-retardant (OP1311) and/ or organonanoclay (Cloisite 30B) is hereby investigated employing thermogravimetric analysis (TGA), to give an insight into their intrinsic behaviour and interaction in polymer nanocomposites for fire safety applications, because the addition of OP1311 and Cloisite 30B in Polyamide 6 (PA6) seems to have a synergistic effect on the thermal decomposition of PA6 (part 2 of the paper). An important objective of this research was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…While, the difference between the TGA curves of PA6+FR and PA6+FR+NC is, however, not significant. It shows that a lot of FR goes to the gas phase as has been detailed in part 1 [11].…”
Section: Tga-ftir Interfacementioning
confidence: 68%
See 1 more Smart Citation
“…While, the difference between the TGA curves of PA6+FR and PA6+FR+NC is, however, not significant. It shows that a lot of FR goes to the gas phase as has been detailed in part 1 [11].…”
Section: Tga-ftir Interfacementioning
confidence: 68%
“…On the other hand, the NC is known to increase char formation and form 'thermal barrier layer' without necessarily increasing the thermal degradation rate (lowering degradation onset temperature). It seems that most of the FR escapes to the gaseous phase (see Part I, [11]). …”
Section: Thermal Degradation In Nitrogenmentioning
confidence: 99%
“…[23,33,34], whereas flame-retarded PMMAs with or without the filler nanoparticles possess additional shoulders around 430e450 C resolved by differential thermogravimetry. These mass loss rate shoulders might be attributed to the evolution of gaseous decomposition products of the organophosphorus flame-retardant [25,26]. Table 4 lists some of the important thermogravimetric data.…”
Section: Characterization Of Fire Residuesmentioning
confidence: 98%
“…In the former mechanism, transport of oxygen and flammable volatiles are impeded, and polymer is shielded from the external radiant heat and the heat feedback of the flame by the act of the protective intumescent layer. The latter mechanism involves the evolution of flame inhibiting phosphorus species together with less-combustible products like melamine contributing to the gasphase action [25,26].…”
Section: Cone Calorimetric Fire Propertiesmentioning
confidence: 99%
“…According to the acting mechanism of alkylphosphinate‐based flame‐retardant systems, one can imagine that the potential flame‐retardant synergism might exist between aluminum phosphinates and organic montmorillonite (OMMT), because OMMT has been widely used as a flame retardant by the formation of multilayered carbonaceous‐silicate barrier on the polymer surface that will insulate the underlying material from the heat flux of the flame and act as a mass transport barrier . Several studies confirmed this speculation that the alkylphosphinate‐based flame retardant and OMMT did have a synergistic effect on polyamide 6 (PA6) . Ramani et al systematically investigated the interaction of a phosphorus‐based flame retardant, a nanoclay, and PA6 and found that the addition of the phosphorus‐based flame retardant and the nanoclay in PA6 seemed to have a synergistic effect on the thermal decomposition of PA6.…”
Section: Introductionmentioning
confidence: 99%